Human Capital Investment and Organizational Performance: A Theoretical Review - Mutua, Jemmy; Kimanthi, Ruth; Kinyili, Jacinta (THE INTERNATIONAL JOURNAL OF HUMANITIES & SOCIAL STUDIES, 2024)
Skill and capacities present in the workforce, if put to productive use, can be vital determinants of a nation's longterm profit gains. Building employees' competence through skill acquisition is an important yardstick in measuring an organization's performance. Keeping into account the importance of investing in human resources in an organization, the current study tries to review existing literature and research work on human capital and organization investment with a main focus on human capital accumulation, human capital depletion and human capital drivers. The study reviewed existing literature that shows the relationship between human capital and organization investment, which shows either a firm performing well or projecting poor performance. The review has shown that human capital accumulation, human capital depletion and human capital drivers have a positive influence on the performance of an organization when proper investment strategies are adopted. The findings also show that organizations that invest in developing their human capital project growth, positive performance and survival of firms in very competitive environments.
Keywords: Human capital investment; human capital drivers; human capital depletion; human capital accumulation; strategic human capital management; resource-based view